A History to Open the Future: Obstacles and Possibilities of Joint History Books in Northeast Asia - Pence Jr, Gary (fi=Turun yliopisto|en=University of Turku|, 2017)
A History to Open the Future is the first history book, published in 2005, to be jointly authored by scholars, teachers, and history activists from China, Japan, and South Korea, and created to be used as a teaching guide for supplementing history lessons on topics ranging from the start of Japanese imperialism, to the end of the Pacific War. A History to Open the Future was created in response to the controversy surrounding the New History Textbook authorized for use in middle schools in Japan in 2001, in which topics such as military Comfort Women and Japanese aggression during the Pacific War were omitted and distorted. A History to Open the Future seeks to overcome said controversy by presenting such contentious topics in Northeast Asia from a perspective of shared history in the region, with the goal of instilling reconciliation and peace in the region. This thesis seeks to understand how the authors, who represent countries with very different and sometimes competing memories of history, came together to create Northeast Asia’s first joint history book and what obstacles existed in that process. Furthermore, this thesis also seeks to discover the possibilities of using such a book in schools in the region. These two research question are answered with data collected from interviews conducted with the authors of the book and teachers in Japan and South Korea. In doing so, this research seeks to shed new light on the history problems plaguing Northeast Asian relations, and provide information on how joint history book may lead to reconciliation in the future.